2009
DOI: 10.1111/j.1467-9787.2008.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Education and Income Inequality in the Regions of the European Union*

Abstract: This paper provides an empirical study of the determinants of income inequality across regions of the EU. Using the European Community Household Panel dataset for 102 regions over the period 1995-2000, it analyses how microeconomic changes in human capital distribution affect income inequality for the population as a whole and for normally working people. The different static and dynamic panel data analyses conducted reveal that the relationship between income per capita and income inequality, as well as betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 58 publications
13
111
1
9
Order By: Relevance
“…The explaining variables include personal characteristic variables, family characteristic variables, and regional characteristic variables. Gender, age and education are included in personal characteristic variables [3]. Family characteristic variables include wage income and non-wage income of other family members, reflecting the impact of family background on individuals [4]; number of kids is also considered as a family characteristic variable, and it can impact on housework and family expenditure, so have further impact on labor force participation.…”
Section: Overview Of Multinomial Logit Modelmentioning
confidence: 99%
“…The explaining variables include personal characteristic variables, family characteristic variables, and regional characteristic variables. Gender, age and education are included in personal characteristic variables [3]. Family characteristic variables include wage income and non-wage income of other family members, reflecting the impact of family background on individuals [4]; number of kids is also considered as a family characteristic variable, and it can impact on housework and family expenditure, so have further impact on labor force participation.…”
Section: Overview Of Multinomial Logit Modelmentioning
confidence: 99%
“…Mahmood et al (2012) in their study obtained results suggesting that educational gap was statistically significant in affecting income inequality. Pose and Tselios (2009) result showed that high levels of inequality in educational attainment are associated with higher income inequality. Their results also showed that ageing population, female participation in the labour force, urbanization, agriculture and industry have a negative effect on inequality, while unemployment and the presence of a strong financial sector positively affect inequality.…”
Section: Literature Reviewmentioning
confidence: 75%
“…These findings indicate that educational factors e.g. higher attainment can contribute to an improvement in income distribution (Rodríguez-Pose & Tselios, 2009). Moreover De Gregorio and from the Universidad de Chile and Korea University investigated that a country with higher educational attainment is more likely to have a more equal income distribution.…”
Section: Education Policymentioning
confidence: 94%